O processo de gramaticalização de e, aí, mas, assim e então em falantes de distintos graus de instrução - Silva, Hugo Henrique Barbosa da (2013)
This research aims to investigate the behavior of the terms e, aí, mas, assim and então used by individuals with different levels of instruction, from the theoretical perspective of functionalist linguistics, specifically from the grammaticalization. Such perspective taken considers language as dynamic, in which the grammar (seen as emergent) is constituted in real use situation, on which is perceived the apparently chaotic regularities. The selection of these terms is justified by the fact that they undergo the process of grammaticalization or discoursivization and they were the most identified ones in this research corpus. It consists of eight interviews (one of them with the teacher and the other ones with their students who live in rural areas and they are enrolled in Youth and Adult Education classes EJA). This work is organized into four parts: introduction, theoretical background, data presentation and analysis, and conclusion. The contributions of Neves (1997), Castillo (2010), Silva (2005), Tavares (2003), Martelotta (1996), among others from the functionalist perspective were used to support this research. Regarding the data presentation and analysis, the quantitative and qualitative elements are demonstrated with the use of graphs, tables and diagrams as well as excerpts from interviews with explanation of how it happened, so the items in questions and the grammaticalization process stages experienced by them can be better understood.